The More the Merrier? The Role of Green Research and Development Subsidies under Different Environmental Policies - Leonie P. Meissner (CESifo GmbH, 2025)
This paper studies the role of green research and development (R&D) subsidies under different environmental policies. Using a stylized equilibrium model calibrated to the European electricity sector, I analyze the effects of R&D subsidies under (1) an emission tax, (2) an emission cap, and (3) no environmental policy, focusing on competitiveness, environmental outcomes, and welfare. I find that increasing R&D subsidies increases knowledge accumulation, reducing production costs and thus, increasing competitiveness of the clean sector. A production shift from dirty to clean output occurs but overall, output increases and lowers output prices. Environmental benefits from R&D subsidies occur only under an emission tax or in the absence of environmental policy. Under an emission cap, emissions remain constant and instead, the emission price falls due to an increase in the R&D subsidy, reducing compliance costs for the emitter. Our calibration further reveals that while patenting is unaffected by the environmental policy, there are interaction effects between the environmental policy stringency and the effectiveness of the R&D subsidy, emphasizing the importance of a policy mix for environmental innovations.
Keywords: D50; H23; O38; Q55; Q58; 330; climate policy; R&D support; innovation policy; renewable energy; environmental innovation